Access to childbirth care services in the interior of Pernambuco, Northeast region of Brazil - Leite, Régia Maria Batista; Araújo, Thália Velho Barreto de; Silva, Maria Rejane Ferreira da; Mendes, Antônio da Cruz Gouveia; Albuquerque, Maria do Socorro Veloso de (Revista de Saúde Pública, 2023)
OBJECTIVE: To analyze the access of women to the public health system network to childbirth care, highlighting the barriers related to the “availability and accommodation” dimension in a health macroregion of Pernambuco. METHODS: Ecological study, conducted based on hospital birth records from the Hospital Information System of the Brazilian Unified Health System (SUS), and information from the state’s Hospital Beds Regulation Center, about women residing in health macroregion II, in 2018. Displacements were reviewed considering the geographic distance between the municipality of residence and that of the childbirth; estimated time of displacement of pregnant women; ratio of shifts blocked for admission of pregnant women for delivery; and the reason for unavailability. RESULTS: In 2018, health macroregion II performed 84% of usual risk childbirths, and 46.9% of high-risk childbirths. The remaining high-risk childbirths (51.1%) occurred in macroregion I, especially in Recife. The reference maternity for high-risk childbirths in that macroregion had 30.4% of the days of day shifts and 38.9% of the night shifts blocked for admission of childbirths; the main reason was the difficulty in maintaining the full team in service. CONCLUSIONS: Women residing in the health macroregion II of Pernambuco face great barriers of access in search of hospital care for childbirth, traveling great distances even when pregnant women of usual risk, leading to pilgrimage in search of this care. There is difficulty regarding availability and accommodation in high-risk services and obstetric emergencies, with shortage of physical and human resources. The obstetric care network in macroregion II of Pernambuco is not structured to ensure equitable access to care for pregnant women at the time of childbirth. This highlights the need for restructuring this healthcare services pursuant to what is recommended by the Cegonha Network.